2010
DOI: 10.5194/bg-7-455-2010
|View full text |Cite
|
Sign up to set email alerts
|

An iron budget during the natural iron fertilisation experiment KEOPS (Kerguelen Islands, Southern Ocean)

Abstract: Abstract. Total dissolvable iron (TDFe) was measured in the water column above and in the surrounding of the Kerguelen Plateau (Indian sector of the Southern Ocean) during the KErguelen Ocean Plateau compared Study (KEOPS) cruise. TDFe concentrations ranged from 0.90 to 65.6 nmol L −1 above the plateau and from 0.34 to 2.23 nmol L −1 offshore of the plateau. Station C1 located south of the plateau, near Heard Island, exhibited very high values (329-770 nmol L −1 ). Apparent particulate iron (Fe app ), calculat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
76
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 50 publications
9
76
0
Order By: Relevance
“…The artificial experiments have indicated an efficiency of biological carbon export into deeper water (100-250 m) ranging from 650 (SERIES, Boyd et al, 2004) to 3300 (mol C/mol Fe) (SOFEX -south, Buesseler et al, 2004). The seasonal sequestration efficiencies estimated for natural Fe fertilization are much higher, 8640 for CROZEX (Pollard et al, 2009) and 154 000 for KEOPS (Chever et al, 2010). The discrepancies in effectiveness between natural and purposeful fertilizations might be partly due to the ∼75% immediate loss of added Fe in artificial fertilisations .…”
Section: Artificial Iron Fertilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The artificial experiments have indicated an efficiency of biological carbon export into deeper water (100-250 m) ranging from 650 (SERIES, Boyd et al, 2004) to 3300 (mol C/mol Fe) (SOFEX -south, Buesseler et al, 2004). The seasonal sequestration efficiencies estimated for natural Fe fertilization are much higher, 8640 for CROZEX (Pollard et al, 2009) and 154 000 for KEOPS (Chever et al, 2010). The discrepancies in effectiveness between natural and purposeful fertilizations might be partly due to the ∼75% immediate loss of added Fe in artificial fertilisations .…”
Section: Artificial Iron Fertilizationmentioning
confidence: 99%
“…In the open ocean, a large variety of naturally iron-fertilized sites exist, which could allow for improved forecasting of the oceanic response to Fe fertilization and a better knowledge of Fe sources to the open ocean. Chever et al (2010) provide a Fe budget for the naturally fertilized area above the Kerguelen Plateau, using total dissolvable Fe as an additional tracer to better constrain the Fe cycle in this area. They show that horizontal advection of water from South of the Plateau seems to be the predominant source of apparent particulate and dissolved iron above the plateau, over atmospheric and vertical inputs.…”
Section: Other Atmospheric and Marine Processes Of Natural Fe Fertilimentioning
confidence: 99%
See 1 more Smart Citation
“…Blain et al (2007) and Chever et al (2010) demonstrated that dFe fertilisation from the plateau increased primary production in the area. From the data gathered it was proposed that resuspension of plateau-derived sediments and entrainment into the mixed layer during increased wind mixing that deepened the mixed layer, was the primary source of particulate and subsequently, dissolved Fe to the downstream blooms.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of the role of the Southern Ocean in CH 4 and N 2 O air-sea exchange may be critical in understanding the factors that influence GHG cycling. This includes dFe which comes from different sources within the KPR, inducing mesotrophic conditions associated with the coastal waters of the Kerguelen Islands and of the central Kerguelen Plateau, an area within the central plateau area of the KPR that demonstrates an annually recurrent phytoplanktonic bloom in the (Blain et al, 2008;Chever et al, 2010), and with the Antarctic PF and other mesoscale structures (Mongin et al, 2008;Lasbleiz et al, 2014).…”
mentioning
confidence: 99%